Acute effect of intermittent high-intensity exercise on inhibitory control performance in female futsal athletes - Julio Cesar Barbosa de Lima Pinto; Leonardo de Sousa Fortes; Arnaldo Luis Mortatti; Mário Antônio de Moura Simim; Renêe de Caldas Honorato; André Igor Fonteles (Revista Brasileira de Ciências do Esporte)
ABSTRACT The aim of the study was to verify the acute effect of high-intensity intermittent exercise on inhibitory control performance in female futsal athletes. Fourteen adult female futsal athletes were randomly subjected to a high-intensity intermittent (HIE) exercise condition and a sedentary condition. Before and after the sessions, tests were applied to evaluate inhibitory control performance (Stroop test, Testinpacs®). A time effect was observed only in the HIE condition (p<0.05). The delta [post-pre] of the response time of the incongruous phase of the Stroop test showed a significant difference between the experimental conditions (p<0.05). Conclusion: The HIE improved acute inhibitory control performance in female futsal athletes.